2020
DOI: 10.1177/2516043520969329
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the types of paediatric adverse events detected by the global trigger tool – CareTrack Kids

Abstract: Introduction A common method of learning about adverse events (AEs) is by reviewing medical records using the global trigger tool (GTT). However, these studies generally report rates of harm. The aim of this study is to characterise paediatric AEs detected by the GTT using descriptive and qualitative approaches. Methods Medical records of children aged 0–15 were reviewed for presence of harm using the GTT. Records from 2012–2013 were sampled from hospital inpatients, emergency departments, general practice and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In total, 48% of all reported clinical incidents for children with intellectual disability in our study were related to medication/intravenous fluid. The Australian CareTrack study, involving the medical records of 6689 children in three Australian states, found 48% of medication/intravenous fluid related incidents in paediatric patients across primary, secondary, and tertiary care settings, using a global trigger tool 31 . Others have found children are particularly susceptible to medication‐related errors when admitted to hospital because of the variable dosing required to account for weight and growth differences, 32–34 which suggests children with complex or chronic medical conditions requiring regular medication may have increased risk of medication errors when in hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 48% of all reported clinical incidents for children with intellectual disability in our study were related to medication/intravenous fluid. The Australian CareTrack study, involving the medical records of 6689 children in three Australian states, found 48% of medication/intravenous fluid related incidents in paediatric patients across primary, secondary, and tertiary care settings, using a global trigger tool 31 . Others have found children are particularly susceptible to medication‐related errors when admitted to hospital because of the variable dosing required to account for weight and growth differences, 32–34 which suggests children with complex or chronic medical conditions requiring regular medication may have increased risk of medication errors when in hospital.…”
Section: Discussionmentioning
confidence: 99%
“…The Australian CareTrack study, involving the medical records of 6689 children in three Australian states, found 48% of medication/intravenous fluid related incidents in paediatric patients across primary, secondary, and tertiary care settings, using a global trigger tool. 31 Others have found children are particularly susceptible to medication‐related errors when admitted to hospital because of the variable dosing required to account for weight and growth differences, 32 , 33 , 34 which suggests children with complex or chronic medical conditions requiring regular medication may have increased risk of medication errors when in hospital. When considered alongside the CareTrack study, our findings contribute toward the enhanced understanding of risk factors related to medication incidents in paediatric health care and provide direction for targeted research and service improvements involving hospitalized children and young people with intellectual disability.…”
Section: Discussionmentioning
confidence: 99%
“…After AEs have been detected with the GTT, their rates may be calculated and displayed graphically over time [ 8 ]. Originally developed for adult inpatients in 2003, the GTT has since been modified for hospital specialties [ 10–13 ] and primary care [ 13–15 ] with a second edition (‘the GTT Protocol’) published in 2009 [ 8 ]. Medical record review, using structured tools like the GTT, is considered to be one of the patient safety data sources most amenable to measuring rates of AEs, whilst IRSs are not suitable for reliable measurement purposes largely owing to reporting biases [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hibbert and colleagues used the CareTrack global trigger tool to identify harm in pediatric practices in three Australian states. 15 They were able to characterize types of adverse events, an important prerequisite for directing improvements.…”
mentioning
confidence: 99%